Effect of Combined Kinesio Taping and Neuro Development Therapy on Sitting Balance in Children with Cerebral Palsy - Virginia Ainurridlo Nugroho; Djoko Witjaksono; Samiah Rachmawati; Nanik Setijowati (Poltekkes Kemenkes Surabaya, 2025)
Cerebral palsy (CP) is a neurological disorder that affects movement and posture. Spastic diplegia and quadriplegia in CP patients, particularly those with GMFCS III, IV, and under five years of age, often require therapeutic interventions to improve functional ability. Neurodevelopment therapy (NDT) is frequently used for this purpose, and the addition of Kinesio Taping (KT) provides additional benefits. This quasi-experimental study focused on children under five years old with spastic diplegia and quadriplegia CP (GMFCS III and IV) at Dr. Saiful Anwar Hospital, East Java. The number of subjects analyzed was 14, divided into two groups, namely Group A, given a combination therapy of KT and NDT (7 subjects), as well as Group B, given NDT (7 subjects). Both groups were subjected to pre-test and post-test assessments using the Trunk Control Measurement Scale after an intervention period of 12 weeks. The results showed that the static sitting balance of both groups had significant improvement after the intervention (p<0.05). This is in accordance with a study conducted by Cubukcu and Karaoglu, which examined 30 patients with spastic CP (diplegia, quadriplegia) aged 2-5 years. A total of 15 patients were put into the neurodevelopmental treatment group (Group A), while 15 were placed into a conventional home exercise program (Group B). However, there was no significant difference between the group receiving the combination of KT with NDT and the group given NDT alone.